CONCEPTUAL METAPHOR OF LOVE IN MINANG SONG CREATED BY SYAHRUL TARUN YUSUF - Sari, Desi Ratna (English Department FBS UNP, 2019)
ABSTRACT This research aims to describe and explain conceptual metaphor of love containing in Minang song created by Syahrul Tarun Yusuf (Satayu). This research is descriptive qualitative. The data are metaphor in Minang song and source of data is a song created by Satayu. The method used is non observational method (SBLC) by using recording and note taking techniques. The methods of analyzing data are translational, referential and pragmatic identity methods. Further, to present the result of analysis data writer uses formal and informal methods. Theory used to analyze conceptual metaphor is Lakoff and Johnson theory. Based on the results of analysis it can be concluded that there are six forms of conceptual metaphors, they are: (1) love is light, (2) love is power, (3) love is longing, (4) love is fearing, (5) love is precious and (6) love is protection. Keywords: conceptual metaphor, song.